2013
DOI: 10.1631/jzus.b1200352
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year monitoring of paddy rice planting area in Northeast China using MODIS time series data

Abstract: Abstract:The objective of this study was to investigate the tempo-spatial distribution of paddy rice in Northeast China using moderate resolution imaging spectroradiometer (MODIS) data. We developed an algorithm for detection and estimation of the transplanting and flooding periods of paddy rice with a combination of enhanced vegetation index (EVI) and land surface water index with a central wavelength at 2 130 nm (LSWI 2130 ). In two intensive sites in Northeast China, fine resolution satellite imagery was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…Our maps are able to show detailed shifts in rice area on the local to county scale, which could not be deduced from the publicly-available agricultural statistics. The biggest observable change during the time period studied is the large increase in rice area in Heilongjiang, which has also been reported by previous studies [36,38,40,42]. From 2005 onward, paddy rice area in Heilongjiang increased at an unprecedented rate.…”
Section: Discussionsupporting
confidence: 81%
“…Our maps are able to show detailed shifts in rice area on the local to county scale, which could not be deduced from the publicly-available agricultural statistics. The biggest observable change during the time period studied is the large increase in rice area in Heilongjiang, which has also been reported by previous studies [36,38,40,42]. From 2005 onward, paddy rice area in Heilongjiang increased at an unprecedented rate.…”
Section: Discussionsupporting
confidence: 81%
“…Based on this approach, continental scale paddy rice maps was generated, covering southern China, South Asia, and Southeast Asia by using 8-day time series MODIS data (Xiao et al, 2006(Xiao et al, , 2005. This method has attracted increasing attention and is now widely used in various geographical regions (Dong et al, , 2016a(Dong et al, , 2016bQin et al, 2015;Shi et al, 2013;Zhang et al, 2015).…”
Section: Category Four: Phenology-based Approaches Through Remote Senmentioning
confidence: 99%
“…Several studies have attempted to improve the phenology-based rice mapping method (Xiao et al, 2005) by defining the flooding and transplanting periods based on observed phenology data from agricultural meteorological stations (Peng, 2009;Peng et al, 2011;Shi et al, 2013). The dependence of these improved methods on agricultural phenology data limited the approach's extensive applications in the regions without observations.…”
Section: Category Four: Phenology-based Approaches Through Remote Senmentioning
confidence: 99%
“…Huamin et al, (2009) menggunakan citra MODIS untuk melihat dinamika musiman indek vegetasi dan karakteristik fenologi gandum dan jagung di China. Shi et al, (2013) (Xiao et al, 2005). Namun, penggunaan citra satelit resolusi spasial moderat dan global telah dibatasi terutama di lahan sawah yang kecil/sempit, karena ada banyak jenis tutupan lahan dalam satu pixel.…”
Section: Abstrakunclassified
“…Metode yang digunakan dalam penelitian ini adalah metode analisis citra MODIS delapan harian meliputi ektraksi indeks (EVI), filter/smoothing dengan metode rata-rata bergerak (moving average) dan median filter (Shi et al, 2013) kemudian pemetaan fase pertumbuhan (sebelum dan setelah smoothing). Selain itu juga dilakukan klasifikasi penutupan/ penggunaan lahan pada citra LANDSAT 8 multiwaktu untuk memperoleh fase pertumbuhan padi (Tabel 3-1) untuk analisis akurasi fase pertumbuhan berbasis MODIS tahap I, sedangkan analisis akurasi tahap II (input hasil model yang tidak di-smoothing) dan III (input hasil model yang di-smoothing).…”
Section: Abstrakunclassified